Analisis Harga, Promosi, dan Kualitas Pelayanan Terhadap Keputusan Pembelian pada Eccindo - Agustin, Adetya Dwi; Supardi, Supardi; Febriansah, Rizky Eka (Universitas Sains dan Teknologi Komputer, 2025)
This study aims to determine the effect of price, promotion and service quality on purchasing decisions at the Eccindo cooperative. This study is a causal study using quantitative methods. The sampling technique used was accidental sampling with a total of 96 respondents who had purchased at the Eccindo cooperative. The data collection technique was by distributing questionnaires. The data analysis technique used Partial Least Square (PLS) using the Smart-PLS Version 3.0 program. The results of this study indicate that. (1) price affects purchasing decisions. (2) promotion affects purchasing decisions. (3) service quality affects purchasing decision.